2014
DOI: 10.1002/acp.3084
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sexually Degrading Music on Men's Perceptions of Women's Dating‐Relevant Cues

Abstract: This study examined the influence of manipulated and naturalistic exposure to sexually degrading music on young men's perceptions of women's dating-relevant affective cues. Three hundred ninety-seven undergraduate heterosexual men completed an affect-identification task in which they judged whether women communicated sexual interest, friendliness, sadness, or rejection. Either sexually degrading popular music, non-sexually degrading popular music, or no music played on headphones. Participants completed questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
14
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 29 publications
4
14
2
5
Order By: Relevance
“…Contrary to expectations and our prior work (e.g., Farris et al, 2006, 2008b, 2010; Treat et al, 2015a), all six bivariate interactions among the cues were unreliable and small in magnitude. The lack of interactions between utilization of affect and the other cues indicated that provocative dress, attractiveness, and sexually relevant contexts did not potentiate reliance on affect when judging women’s sexual interest on a continuous rating scale.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to expectations and our prior work (e.g., Farris et al, 2006, 2008b, 2010; Treat et al, 2015a), all six bivariate interactions among the cues were unreliable and small in magnitude. The lack of interactions between utilization of affect and the other cues indicated that provocative dress, attractiveness, and sexually relevant contexts did not potentiate reliance on affect when judging women’s sexual interest on a continuous rating scale.…”
Section: Discussioncontrasting
confidence: 99%
“…Our prior work with affective classification tasks (rather than continuous-rating tasks) revealed interactive effects of affective and non-affective cues based on their congruence: men showed greater sensitivity to a sexual-interest cue when women were provocatively dressed or attractive and greater sensitivity to a rejection cue when women were conservatively dressed or unattractive (Farris et al, 2006, 2008b, 2010; Smith et al, under review; Treat et al, 2015a). The extent to which pairwise cue combinations influence men’s continuous sexual-interest judgments over and above the independent contributions of the cues to such judgments has been unknown, however.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High-risk men, relative to low-risk men, show deficiencies in attention to, sensitivity to, memory for, and decision-making about women’s sexual-interest, as communicated nonverbally on a woman’s face and in her body posture in full-body photographs (e.g., Treat, Farris, Viken, & Smith, 2015; Treat, Viken, Farris, & Smith, in press; Treat, Viken, Kruschke, & McFall, 2011; see Figure 1 for sample images). These deficits could foster misperception or potential dismissal of women’s sexual non-consent cues as token resistance or as purposely inciting frustration.…”
mentioning
confidence: 99%